Enhancing Elementary Students’ Creativity and Understanding through Audio-Visual Learning Media - Khasanah, Nur; Muhajir; Soubar Isman (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
The purpose of this research is to determine whether audio-visual-based learning media influence the creativity and understanding of fifth-grade students at SDN Mlajah 2 Bangkalan in the IPAS subject of human body process. This research uses a quantitative methodology with comprehension questions and questionnaires as research tools. 30 students from class V-A and 30 students from class V-B formed the sample, with a total of 60 students in this research. This research uses a saturated sampling strategy. The IBM SPSS v.21 statistical application for Windows, which includes analysis tools such as validity tests, reliability tests, homogeneity tests, normality tests, and independent sample T-tests, was used to process the data in this research. Based on the findings from the independent sample T-test used for hypothesis testing, learning creativity has a significant value of 0.000 < 0.05, indicating that learning creativity is impacted by audio-visual learning media. The independent sample T-test on student understanding shows a significance value of 0.000 < 0.05, indicating that audio-visual learning media affects student understanding in the IPAS subject in the fifth grade at SDN Mlajah 2 Bangkalan.